Update of Potential Biomarkers in Risk Prediction and Monitoring of Atherosclerosis in Systemic Lupus Erythematosus to Prevent Cardiovascular Disease - Dominika Blachut; Brygida Przywara-Chowaniec; Andrzej Tomasik; Tomasz Kukulski; Beata Morawiec (Biomedicines, 2023)
Systemic lupus erythematosus is a chronic connective tissue disease associated with an increased risk of premature atherosclerosis. It is estimated that approximately 10% of SLE patients develop significant atherosclerosis each year, which is responsible for premature cardiovascular disease that is largely asymptomatic. This review summarizes the most recent reports from the past few years on biomarkers of atherosclerosis in SLE, mainly focusing on immune markers. Persistent chronic inflammation of the vascular wall is an important cause of cardiovascular disease (CVD) events related to endothelial dysfunction, cell proliferation, impaired production and function of nitric oxide and microangiopathic changes. Studies on pathogenic immune mediators involved in atherosclerosis will be crucial research avenues for preventing CVD.